Indigenous Peoples, Representation and Citizenship in Guatemalan Forestry - Larson, A.M. (2008)
Forestry decision-making is still largely centralised in Guatemala. Nevertheless, elected municipal governments can now play a key role in local forest management. These local governments, with some exceptions, are the principal local institutions empowered to participate in natural resource authority. Some theorists argue that such elected local officials are the most likely to be representative and downwardly accountable. But do these political institutions have the ability to represent the interests of minority and historically excluded or oppressed groups? Latin American indigenous movements are fighting for new conceptions of democracy and practices of representation that recognise collective rights and respect for customary law and authority. How does this approach weigh against elected local government? This article compares how elected municipal governments versus traditional indigenous authorities represent the interests of indigenous communities in forest management. It traces the historical context of relations between indigenous people and the state in the region, and then presents the findings from case studies in two Guatemalan municipalities. The article finds that both authorities have some strengths as well as important weaknesses, thus supporting arguments for the reinvention of both liberal democracy and tradition in the interest of inclusive citizenship